Melastoma malabathricum (L.) Smith Ethnomedicinal uses, chemical constituents, and pharmacological properties: A review. - Mohd. Jofrry, S.; Yob, N. J.; Rofiee, M. S.; Meor Mohd. Affandi, M. M. R.; Suhaili, Z.; Othman, Fezah; Md. Akim, Abdah; Mohd Desa, Mohd Nasir; Zakaria, Zainul Amiruddin (Hindawi Publishing Corporation, 2012)
Melastoma malabathricum L. (Melastomataceae) is one of the 22 species found in the Southeast Asian region, including Malaysia. Considered as native to tropical and temperate Asia and the Pacific Islands, this commonly found small shrub has gained herbal status in the Malay folklore belief as well as the Indian, Chinese, and Indonesian folk medicines. Ethnopharmacologically, the leaves, shoots, barks, seeds, and roots of M. malabathricum have been used to treat diarrhoea, dysentery, hemorrhoids, cuts and wounds, toothache, and stomachache. Scientific findings also revealed the wide pharmacological actions of various parts of M. malabthricum, such as antinociceptive, anti-inflammatory, wound healing, antidiarrheal, cytotoxic, and antioxidant activities. Various types of phytochemical constituents have also been isolated and identifed from different parts of M. malabathricum. Thus, the aim of the present review is to present comprehensive information on ethnomedicinal uses, phytochemical constituents, and pharmacological activities of M. malabathricum.